2022
DOI: 10.1177/00914509221105285
|View full text |Cite
|
Sign up to set email alerts
|

Local Prohibitions on Marijuana: Factors Associated With Bans on Medical and Recreational Businesses

Abstract: Marijuana legalization in U.S. states has introduced new regulatory processes, which allow for some degree of local authority. A common provision in state laws has provided a local option, which enables municipalities to prohibit commercial cannabis facilities within their borders. This paper examined potential determinants of prohibition decisions, with an emphasis on community and local government characteristics. Using a multivariate logistic regression model, determinants of local decisions to prohibit can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Under this assumption, marijuana businesses may disproportionately locate in poorer communities that lack the financial resources or political influence to challenge them by enacting local ordinances or zoning regulations. This explanation would align with prior analyses of local prohibitions on marijuana businesses, which found a higher likelihood of adopting a ban among communities with higher income levels and lower proportions of racial minorities (Matthay et al, 2022a ; Matthay et al, 2022b ; Moiseeva 2023 ; Yaskewich 2022 ; Yaskewich 2023 ). However, alternative hypotheses suggest that socioeconomic deprivation still may attract retail outlets even if they are not perceived as LULUs.…”
Section: Literature Reviewsupporting
confidence: 79%
“…Under this assumption, marijuana businesses may disproportionately locate in poorer communities that lack the financial resources or political influence to challenge them by enacting local ordinances or zoning regulations. This explanation would align with prior analyses of local prohibitions on marijuana businesses, which found a higher likelihood of adopting a ban among communities with higher income levels and lower proportions of racial minorities (Matthay et al, 2022a ; Matthay et al, 2022b ; Moiseeva 2023 ; Yaskewich 2022 ; Yaskewich 2023 ). However, alternative hypotheses suggest that socioeconomic deprivation still may attract retail outlets even if they are not perceived as LULUs.…”
Section: Literature Reviewsupporting
confidence: 79%
“…Further analyses of prohibitions on marijuana-related businesses focused on local policy outcomes in states that legalized recreational marijuana. When Michigan granted local authority to opt out of recreational marijuana sales, Yaskewich (2022) estimated that the likelihood of prohibition was positively associated with median household income, but it was negatively associated with the proportions of residents who were below age 65 and Black. In a similar vein, Camors, Chavez, and Romi’s (2020) analysis of Oregon cities also found less tolerance of commercial marijuana activities among more affluent communities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior studies have identified factors associated with local prohibitions on retail sales of marijuana in early adopting states, such as Oregon (Camors, Chavez, & Romi, 2020) and Michigan (Yaskewich, 2022). However, it is not clear whether their results can be generalized to other states or commercial activities.…”
mentioning
confidence: 99%